Os efeitos diretos e indiretos da mentalização interpessoal no desempenho de vendas - Senra, Karin Borges (2016)
A recent study in sales is the ability of interpersonal mentalizing. Few researchers have attempted to understand the ability of interpersonal mentalizing in this context. More specifically, research exploring the indirect effects that interpersonal mentoring can have on performance were not found. This work was based on the concept of interpersonal mentalizing of salespeople, which relates to other sales skills. Salespeople interpersonal mentalizing skills refers to the interpretation of interpersonal situation, and then mentalizes about the customers, in particular, through a process of making inferences as to the beliefs, desires, intentions, and other mental states of the customer. The main objective of this work was to examine the role of salespeople interpersonal mentalizing such as direct and indirect determinant of performance. A theoretical model of simple multiple mediation was created. The model assumes that interpersonal mentalizing, through each of its dimensions, has a positive relationship with performance and that the constructs of self-efficacy and adaptive sellling have mediating role on the relationship between the dimensions of interpersonal mentalizing and performance. A survey was conducted with 250 salespeople, in two different samples in the city of Maringa - Parana. The results indicate that the dimensions of interpersonal mentalization perform positive direct and indirect effects on sales performance. The competencies of self-efficacy and adaptive selling were mediators on the effects of interpersonal mentalizing in performance. An additional model was developed resulting that such competencies also conduct a serial mediation on the relationship between interpersonal mentalizing and performance. The results are according to the literature. Theoretical and managerial implications, limitations and future research suggestions are discussed.